2017
DOI: 10.1002/1873-3468.12752
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into a secretory abundant heat‐soluble protein from an anhydrobiotic tardigrade,Ramazzottius varieornatus

Abstract: Upon stopping metabolic processes, some tardigrades can undergo anhydrobiosis. Secretory abundant heat-soluble (SAHS) proteins have been reported as candidates for anhydrobiosis-related proteins in tardigrades, which seem to protect extracellular components and/or secretory organelles. We determined structures of a SAHS protein from Ramazzottius varieornatus (RvSAHS1), which is one of the toughest tardigrades. RvSAHS1 shows a β-barrel structure similar to fatty acid-binding proteins (FABPs), in which hydrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 64 publications
(73 reference statements)
2
48
0
Order By: Relevance
“…B ‐factor values showed that the lid region of Rv SAHS4 was highly flexible (Fig. S1, Supporting Information), as is observed in Rv SAHS1 . The variety of residues and the flexibility in the lid structure may be related to ligand binding.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…B ‐factor values showed that the lid region of Rv SAHS4 was highly flexible (Fig. S1, Supporting Information), as is observed in Rv SAHS1 . The variety of residues and the flexibility in the lid structure may be related to ligand binding.…”
Section: Resultsmentioning
confidence: 76%
“…The overall structure of Rv SAHS4 shared a typical FABP fold having an antiparallel β‐barrel composed of 10 β‐strands, and a helix‐turn‐helix lid between βA and βB. Because main chain atoms could not form hydrogen bonds between βD and βE, there was a gap as is found in Rv SAHS1 and FABPs . The N‐terminal region of the adjacent molecule was inserted into this gap in the crystal structure [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations